SIRT3 Protects Against Acute Kidney Injury via AMPK/mTOR-Regulated Autophagy - Zhao, Wenyu; Zhang, Lei; Chen, Rui; Lu, Hanlan; Sui, Mingxing; Zhu, Youhua; Zeng, Li (Frontiers in Physiology, 2018)
Acute kidney injury (AKI) is an important public health problem involving the loss of kidney function caused by damage to renal tubular cells. We previously showed that sirtuin (SIRT)3 protects against mitochondrial damage in the kidneys by inhibiting the NRLP3 inflammasome, attenuating oxidative stress, and downregulating proinflammatory cytokines. Here, we investigated the role of autophagy mediated by mammalian target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK) in the protective effect of SIRT3 against sepsis-induced AKI in a mouse model of cecal ligation and puncture (CLP). AKI in CLP mice was associated with upregulation of autophagy markers, and this effect was abolished in SIRT3−/− mice in parallel with downregulation of phospho (p)-AMPK and upregulation of p-mTOR. Pretreatment with the autophagy inhibitor 3-methyladenine or AMPK inhibitor compound C exacerbated AKI. SIRT3 overexpression promoted autophagy, upregulated p-AMPK, and downregulated p-mTOR in CLP mice, attenuating sepsis-induced AKI, tubular cell apoptosis, and inflammatory cytokine accumulation in the kidneys. Blockade of autophagy induction largely abolished the protective effect of SIRT3 in sepsis-induced AKI. These findings indicate that SIRT3 protects against CLP-induced AKI by inducing autophagy through regulation of the AMPK/mTOR pathway.